Oxygen-transfer from N2O to CO via Y-doped Ti2CO2 (MXene) monolayer at room temperature: Density functional theory and ab initio molecular simulation studies - Yu, Yang-Xin (Journal of colloid and interface science, 2025)
[Display omitted] •Stability of Sc-, Y-, Ti-, Zr- and Hf-doped MXenes are identified theoretically.•N2O + CO reaction paths are analyzed via both redox and associative mechanisms.•Energetic span for reaction N2O + CO on the Y-Ti2CO2 nanosheet is only 4.07 kcal/mol.•An energy descriptor is designed with a linear correlation coefficient of 0.99975.•Y-doped MXene is a promising room-temperature catalyst for the N2O + CO reaction. Nitrous oxide (N2O) contributes to global warming and its reduction by carbon dioxide (CO) offers a promising way to mitigate N2O emissions. However, available catalysts lack high activities at low temperatures. Herein, the catalytic activity of transition-metal-doped Ti2CO2 monolayers (MXenes) are identified theoretically. It is unraveled that Sc-, Y-, Ti- and Zr-doped MXenes exhibit both thermodynamically and dynamically stable while Hf-MXene is dynamical stable. The obtained energy profiles, activation barriers and energetic spans are compared. A new descriptor considering synergy effects of promotion energy, ionization potential and d-electron number is proposed for the energetic span with a linear correlation coefficient of 0.9998. The Y-doped MXene stands out as an ideal catalyst which is further validated using the ab initio molecular dynamics simulations at 298.15 K. This work offers not only an excellent room-temperature catalyst for N2O + CO reaction, but also a descriptor for chemical reactions with a high correlation.